Removal Characteristics of Sapphire Lapping using Composite Plates with Consciously Patterned Resinoid-Bonded Semifixed Diamond Grits - Wenshan Wang; Yiqing Yu; Zhongwei Hu; Congfu Fang; Jing Lu; Xipeng Xu (Crystals, 2020)
Sapphire lapping is of key importance for the successful planarization of wafers that are widely present in electronic devices. However, the high hardness of sapphire makes it extremely challenging to improve its material removal rate during the lapping process without compromising surface quality and dimensional accuracy. In this work, a novel composite lapping plate consisting of a rigid resin frame and flexible sol–gel balls was fabricated with consciously designed patterns. Through lapping experiment, it was revealed that the diamond grits imbedded in the sol–gel balls can effectively lap the sapphire at a promising material removal rate (MRR), without the formation of undesirable scratches and loss of surface integrity. Moreover, by designing the arrangement patterns of sol–gel balls, the total thickness variation (TTV) can also be ensured for lapped sapphire substrates. The implications of experimental results were also discussed based on the trajectory analysis and contact mechanics of lapping grits in order to demonstrate the potential of the newly developed composite abrasive tools for sapphire-lapping applications.